Professional Support Beyond Initial Teacher Education Pedagogical Discernment and the Influence of Out-of-Field Teaching Practices - Du Plessis, Anna Elizabeth; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2019)
This book investigates the professional learning needs of teachers beyond initial teacher education, focusing on teachers in complex teaching positions, such as out-of-field teaching practices. The information presented here will help to improve professional learning strategies, while also offering an in-depth understanding of teachers$1 (Bneeds, leaders$1 (Bperceptions, and what complex teaching situations mean for teachers$1 (Bprofessional learning and development. Further, Du Plessis shares the perceptions and lived experiences of teachers, parents, leaders and students as key stakeholders in quality teaching and learning environments. In light of new evidence-informed findings on the out-of-field phenomenon and continuing professional learning, Du Plessis puts forward strategies that will enhance the effectiveness of professional learning and development programs, while also fostering improved decision-making and policy development. In brief, Du Plessis focuses on the impact that complex teaching situations have on teachers$1 (Bunique needs, the support that is provided, and the influence of the out-of-field phenomenon on teachers$1 (Bresponses to continuing professional learning and development programs. Anna Du Plessis has completed two doctoral degrees in education. Her research in South Africa and in Australia is into what happens when teachers constantly teach outside their areas of expertise. Demand for quality student results and individualized teaching remains. Principals need to be financial administrators as well as education leaders. Teaching involves life-long learning. With appropriate support, teachers and their students thrive. Yet teacher retention plummets internationally. This book reveals the day-to-day reality for teachers, subject specialists and school leaders. You will read the words of the enthusiastic, the burnt out, the tired but hopeful and those resigned to the dilemmas of working in education. It introduces the theory of context-conscious understanding development (C-CUD theory) and the CANNAS leadership model which encourage a school culture supporting targeted professional development and learning. Organizational recommendations are made to shape and sustain a quality teaching workforce beyond initial teacher education. Julie Martyn, Editor, Swinburne University Online, Melbourne, Australia.s
Part I Introduction to Professional Support Considerations -- 1 Education Quality, ITE and Further Professional Support Cultivating Pedagogical Thoughtfulness -- 2 A Context-conscious Theoretical Framing of the Teaching Space -- 3 School Leaders and Professional Support: The Cannas Leadership Model -- 4 The 'Footprint' of Initial Teacher Education: Influencing the Workplace and Beyond -- Part II From ITE to the Workplace -- 5 The Meaning of Complex Teaching Contexts for Support Approaches -- 6 Organisational Culture's Impact on Professional Opportunities and Teaching Quality -- 7 Modalities of Professional Support and their Impact -- 8 The Way Forward.
Keywords: Teaching; Professional education; Vocational education; Learning; Instruction; Educational policy; Education and state; Teaching and Teacher Education; Professional & Vocational Education; Learning & Instruction; Educational Policy and Politics